Non-perturbation theory of electronic dynamic conductivity for two-barrier resonance tunnel nano-structure - Tkach, M.V.; Seti, Ju.O.; Voitsekhivska, O.M. (Condensed Matter Physics, 2011)
The non-perturbation theory of electronic dynamic conductivity for open two-barrier resonance tunnel structure is established for the first time within the model of rect angular potentials and different effective masses of electrons in the elements of nano-structure and the wave function linear over the intensity of electromagnetic field. It is proven that the results of the theory of dynamic co nductivity, developed earlier in weak signal approximation within the perturbation method, qualitatively and quantitatively correlate with the obtained results. The advantage of non-perturbation theory is that it can be extended to the case of electronic currents interacting with strong electromagnetic fields in open multi-shell reso nance tunnel nano-structures, as active elements of quantum cascade lasers and detectors. Вперше запропоновано непертурбацiйну теорiю електронної динамiчної провiдностi вiдкритої дво-бар’єрної резонансно-тунельної структури у моделi прямокутних потенцiалiв i рiзних ефективних мас електронiв у рiзних елементах наносистеми та з лiнiйною за напруженiстю електромагнiтного поля хвильовою функцiєю системи. Показано, що результати розвинутої ранiше теорiї динамiчної провiдностi у малосигнальному наближеннi (у межах теорiї збурень) якiсно i кiлькiсно корелюють з отриманими результатами. Переваги непертурбацiйної теорiї в тому, що вона може бути поширена на випадок взаємодiї потокiв електронiв з потужними електромагнiтними полями у вiдкритих багатошарових резонансно-тунельних наноструктурах, як активних елементах квантових каскадних лазерiв i детекторiв.